Proceedings of the First International Conference on Intelligent Interactive Technologies and Multimedia 2010
DOI: 10.1145/1963564.1963610
|View full text |Cite
|
Sign up to set email alerts
|

A writer-independent off-line signature verification system based on signature morphology

Abstract: In this work, we address off-line signature verification as a writer-independent system. We propose a set of morphological features, extracted from off-line signature images. To examine the effectiveness of the features, a publicly available signature database, namely CEDAR signature database is used. A pair of signatures is fed to the system to give an inference for their (dis)similarity. To get a compact set of features, a multilayer perceptron based feature analysis technique is utilized. A 10-fold cross-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The evaluation was carried out on all the 55 sets. Table 1 compares the error rates and the accuracy against the existing methods, of which [8] and [9] are person independent. FRR keeps decreasing from FRBS contrast intensification to FRFS in the proposed methods implying that forgeries are being identified more accurately by contrast enhancement and feature selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation was carried out on all the 55 sets. Table 1 compares the error rates and the accuracy against the existing methods, of which [8] and [9] are person independent. FRR keeps decreasing from FRBS contrast intensification to FRFS in the proposed methods implying that forgeries are being identified more accurately by contrast enhancement and feature selection.…”
Section: Resultsmentioning
confidence: 99%
“…Larkins et al [10] introduced adaptive feature thresholding (AFT) combined with spatial pyramids [11] and equimass sampling grids [3] for feature extraction using gradient direction and achieved 90% accuracy. Kumar et al [8] proposed a set of morphological features for extraction and multi-layer perceptron (MLP) and support vector machine (SVM) for classification and obtained an accuracy of 88.4%. Kumar et al [9] proposed a set of features based on Surroundedness property of a signature image and based on MLP and SVM obtained an accuracy of 91.67%.…”
Section: Related Workmentioning
confidence: 99%
“…Several applications have been developed based on one of the accurate classifier called Support Vector Machine(SVM). The goal of SVM is to produce a model (based on the training data) which predicts the target values of the test data given only the test data attributes [ (Hsu et al, 2003), (Kumar et al, 2010a)] . Any classification task usually involves separating data into training and testing sets.…”
Section: Classification Based On Svmmentioning
confidence: 99%
“…From the literature we observed that, Kalera et al, (Kalera et al, 2004), Chen and Shrihari (Chen and Srihari, 2005) and Kumar et al, (Kumar et al, 2010b) have experimented on CEDAR dataset and hence a comparative analysis is given in Table 3.…”
Section: Experimentation On Cedar Datasetmentioning
confidence: 99%
“…Solar et al [11] concentrated on local interest points and descriptors for off-line signature verification. Kumar et al [7] presents a novel set of features based on surroundedness property of a signature image to provide a measure of texture through the correlation among signature pixels. To examine the efficacy they used two popular classifiers, SVM and MLP on CEDAR and GPDS dataset.…”
Section: Introductionmentioning
confidence: 99%